Superior Colliculus Responses to Attended, Unattended, and Remembered Saccade Targets during Smooth Pursuit Eye Movements - Dash, Suryadeep; Nazari, Sina Alipour; Yan, Xiaogang; Wang, Hongying; Crawford, J. Douglas (Frontiers in Systems Neuroscience, 2016)
In realistic environments, keeping track of multiple visual targets during eye movements likely involves an interaction between vision,top-down spatial attention, memory, and self-motion information. Recently we found that the superior colliculus (SC) visual memory response is attention-sensitive and continuously updated relative to gaze direction. In that study,animals were trained to remember the location of a saccade target across an intervening smooth pursuit (SP) eye movement (Dash et al. 2015). Here, we modified this paradigm to directly compare the properties of visual and memory updating responsesto attended and unattended targets.Our analysis shows that during SP, active SC visual vs. memory updating responses share similar gaze-centered spatio-temporal profiles (suggesting a common mechanism), but updating was weaker by 25%, delayed by 55ms, and far more dependent on attention. Further, during SP the sum of passive visual responses (to distracter stimuli) and memory updating responses (to saccade targets) closely resembled the responses for active attentional tracking of visible saccade targets. These results suggest that SP updating signals provide a damped, delayed estimate of attended location that contributes to the gaze-centered tracking of both remembered and visible saccade targets.